Desalination and Wastewater Reuse as Technological Alternatives in an Arid, Tourism Booming Region of Mexico - Pombo, Alberto; Breceda, Aurora; Valdez Aragón, Alva (Frontera Norte, 2017)
Los Cabos, Baja California Sur, is one of Mexico’s most popular tourist destinations. With 25% of the state’s population, it has one of the highest population growth rates in the country mostly due to large-scale tourism development. Economic and population growth mean greater water consumption. The region’s main water source is the San José aquifer is overexploited. Private desalinization plants as well as wastewater reclamation plants are becoming important alternative technologies for water management at resort hotels. The projections for population growth and water consumption in the region are alarming. Clearly, there is an urgent need to design renewable resources management strategies, diversify technological alternatives, and design public policies to face the challenges of the future. RESUMEN Los Cabos, Baja California Sur, es uno de los destinos turísticos más populares de México. Alberga 25% de la población del estado y presenta uno de los mayores índices de crecimiento demográfico del país, debido principalmente al desarrollo turístico de gran escala. El desarrollo económico y demográfico demanda un mayor consumo de agua, cuya principal fuente de abastecimiento de la región, el acuífero de San José, se encuentra sobreexplotado. La utilización de plantas desaladoras de agua de mar, de propiedad privada, así como de plantas para reúso de aguas negras se ha convertido en un factor fundamental en las estrategias de manejo del agua de los desarrollos hoteleros. No obstante, dadas las alarmantes proyecciones de crecimiento poblacional y de consumo de agua en la región, resulta imperioso desarrollar nuevas estrategias de manejo de los recursos, diversificar las alternativas tecnológicas y diseñar nuevas políticas públicas para enfrentar los desafíos regionales.